Crystal structure and Hirshfeld surface analysis of chlorido(2,6-dimethylphenyl isocyanide)[N′-(2,6-dimethylphenyl)-N-(pyridin-2-yl)carbamimidoyl]platinum(II) - Olga V. Repina; Elena Yu. Nevskaya; Ilya S. Kritchenkov; Victor N. Khrustalev; Alexander S. Novikov; Alexander G. Tskhovrebov; Namiq Q. Shikhaliyev; Aytan A. Niyazova; Mehmet Akkurt; Ajaya Bhattarai (Acta Crystallographica Section E: Crystallographic Communications)
In the title compound, [Pt(C14H14N3)Cl(C9H9N)], the platinum atom has a square-planar geometry. In the crystal, dimers with R22(8) motifs are formed by pairs of N—H...N hydrogen bonds. They are connected to each other through pairs of weak C—H...Cl interactions, forming a R22(16) motif, creating parallel ribbons along the [011] axis. The molecular pairs are also linked by C—H...π and by π–π interactions, the shortest centroid-centroid distance [3.513 (2) Å] being observed between pyridyl rings. These weak interactions form parallel ribbons along the [010] axis. The resulting three-dimensional network ensures the cohesion of the crystal structure. Hirshfeld two-dimensional fingerprint plots revealed that the most significant interactions are H...H (58.0%), C...H/H...C (17.9%), Cl...H/H...Cl (10.7%), N...H/H...N (6.9%), C...C (2.9%), Pt...H/H...Pt (2.6%), and N...C/C...N (1.1%) contacts.